2000
DOI: 10.1159/000052047
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Profile of Alcohol Consumption Patterns of Police Officers in a Large Scale Sample of an Australian Police Service

Abstract: The current study aimed to examine the prevalence of alcohol use within a large sample (n = 4,193) of Australian police offers. Prevalence and at risk behaviour was measured through the use of a self-report survey containing the AUDIT and standard frequency and quantity questions. Results indicated that although police did not report drinking with high frequency when compared to the national statistics, they did drink in far greater quantities. Further, both males and females in the police sample reported high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 12 publications
5
46
1
Order By: Relevance
“…Besides, an excess risk of gallbladder cancer was also observed for female public safety workers, who were mainly police. A high level of alcohol consumption was observed for female policemen in a recent Australian study (Davey et al 2000). Other occupational groups with a high alcohol intake, such as waiters and seamen, did not show an excessive risk of gallbladder cancer in the present study.…”
Section: Discussionsupporting
confidence: 50%
“…Besides, an excess risk of gallbladder cancer was also observed for female public safety workers, who were mainly police. A high level of alcohol consumption was observed for female policemen in a recent Australian study (Davey et al 2000). Other occupational groups with a high alcohol intake, such as waiters and seamen, did not show an excessive risk of gallbladder cancer in the present study.…”
Section: Discussionsupporting
confidence: 50%
“…The prevalence of heavy alcohol consumption found in the current study was considerably lower than that found in studies that have used the same assessment instrument in ERI AND ALCOHOL 13 relation to United Kingdom vets (Bartram, 2009) and Australian police (Davey, Obst, & Sheehan, 2000). Our findings are similar to those found among police and ambulance personnel in Norway (Sterud et al, 2007).…”
Section: Discussionsupporting
confidence: 69%
“…A study by Davey, Obst, and Sheehan (2000) of a large sample of Australian police officers found that 30% of officers scored in the "at risk of harmful consumption" category on the World Health Organizations Alcohol Use Disorders Identification Test (AUDIT) while 3% scored in the 'alcohol dependant' category. At examination, male officers, officers 18-35 years of age, those divorced or separated, constables and operational personnel, and officers who have served between 4-10 years were the groups most likely to fall in these risk categories.…”
Section: Police Alcohol Usementioning
confidence: 99%
“…The Alcohol Use Disorders Identification Test (AUDIT) developed by the World Health Organization (WHO) has been found to be an appropriate and reliable measure of alcohol use across gender, age, and race (Saunders, Aasland, Babor, Fuente, & Grant, 1993;Steinbauer, Cantor, Holzer, & Volk, 1998;Volk, Steinbauer, Cantor, & Holzer, 1997), as well as an appropriate and reliable indicator of potentially damaging levels of consumption in the United States (Dawson, Grant, Stinson, & Zhou, 2005) and among law enforcement officers (Davey et al, 2000;Lindsay & Shelley, 2009). A within sample analysis resulted in a Chronbach alpha of 0.77.…”
Section: Auditmentioning
confidence: 99%